Elucidation of Echovirus 30's Origin and Transmission during the 2012 Aseptic Meningitis Outbreak in Guangdong, China, through Continuing Environmental Surveillance - Lu, Jing (Appl Environ Microbiol, 2015)
An aseptic meningitis outbreak occurred in Luoding City of Guangdong, China, in 2012, and echovirus type 30 (ECHO30) was identified as the major causative pathogen. Environmental surveillance indicated that ECHO30 was detected in the sewage of a neighboring city, Guangzhou, from 2010 to 2012 and also in Luoding City sewage samples (6/43, 14%) collected after the outbreak. In order to track the potential origin of the outbreak viral strains, we sequenced the VP1 genes of 29 viral strains from clinical patients and environmental samples. Sequence alignments and phylogenetic analyses based on VP1 gene sequences revealed that virus strains isolated from the sewage of Guangzhou and Luoding cities matched well the clinical strains from the outbreak, with high nucleotide sequence similarity (98.5% to 100%) and similar cluster distribution. Five ECHO30 clinical strains were clustered with the Guangdong environmental strains but diverged from strains from other regions, suggesting that this subcluster of viruses most likely originated from the circulating virus in Guangdong rather than having been more recently imported from other regions. These findings underscore the importance of long-term, continuous environmental surveillance and genetic analysis to monitor circulating enteroviruses.